Ammonia volatilization and marandu grass evaluation under doses and sources of nitrogen fertilizers (Research, Society and Development, 2020)
The present study was conducted with the objective of evaluating the dry matter production of the aerial part and crude protein content of the Urochola brizantha cv. Marandu, in addition to the losses of ammonia (N-NH3) by volatilization and the efficiency of fertilizing sources of nitrogen fertilizers and applied nitrogen doses. The experimental design was in randomized blocks, with four replications, in a 3x3 factorial scheme, the treatments consisted of the combination of three nitrogen sources (urea, urea with polymer and urea with urease inhibitor NBPT (N- (n-butyl) thiophosphoric triamide) ), three doses of N (50,100 and 150 kg ha-1 of N) and the control (without fertilization) constituting 10 treatments, with four repetitions. The nitrogen source that showed the lowest ammonia losses (N-NH3) through volatilization was urea treated with urease inhibitor (NBPT), the peak of volatilization occurred on the second day after nitrogen application. The doses of N influenced the DMP, CP and ammonia volatilization, therefore, they must be considered in the determination of strategies in the management of the pasture.